Clinical and Radiographic Comparison Between Open Versus Minimally Invasive Transforaminal Lumbar Interbody Fusion With Bilateral Facetectomies. Issue 6 (July 2021) - Le, Hai; Anderson, Ryan; Phan, Eileen; Wick, Joseph; Barber, Joshua; Roberto, Rolando; Klineberg, Eric; Javidan, Yashar
Study Design: Age- and sex-matched cohort study. Objectives: To compare outcomes after open versus minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) with bilateral facetectomies. Methods: We retrospectively compared patients who underwent single- or 2-level MIS-TLIF with an age- and sex-matched open-TLIF cohort. Surgical data was collected for operative time, estimated blood loss (EBL), and drain use. Clinical outcomes included the Visual Analog Scale (VAS), Oswestry Disability Index (ODI), length of stay (LOS), complications, and reoperations. Lumbar radiographs were measured for changes in global lumbar lordosis (LL) and segmental lordosis (SL). Results: Between 2016 and 2020, 38 MIS-TLIF patients were compared with 38 open-TLIF patients. No subfascial drain was used in the MIS-TLIF group ( P < .001). The MIS-TLIF group had longer operative time (310.8 vs 276.5 minutes; P = .046) but less EBL (282.4 vs 420.8 mL; P = .007). LOS ( P = .15), complication rates ( P = .50), and revision rates ( P = .17) were equivalent. VAS and ODI improved but did not differ between groups. In the open-TLIF group, LL and SL were restored or improved in 81.6% and 86.9% of cases, respectively. In the MIS-TLIF group, LL and SL were restored or improved in 86.8% and 97.4% of cases, respectively. There were no differences in changes in LL and SL between groups. Conclusions: Compared with the age- and sex-matched open-TLIF cohort, patients undergoing MIS-TLIF had reduced EBL and subfascial drain use but increased operative time. There were no differences in complications, reoperations, or LOS. Both groups demonstrated improvement in VAS and ODI. MIS-TLIF with bilateral facetectomies provided equivalent improvements in global and segmental LL.